Biomonitoring, distribution and risk assessment of heavy metals and polycyclic aromatic hydrocarbons in Asystasia gangetica (L.) T. Anderson and surrounding topsoil from Peninsular Malaysia - Chew, Weiyun (2016)
In this study, the invasive weed Asystasia gangetica with their surrounding topsoil (0 - 10cm) were collected at 23 sites from Peninsular Malaysia. Samples were collected throughout Peninsular Malaysia during the period of 8th June 2011 to 17th January 2012. The plants (leaves, stems, and roots) and topsoil samples were determined for heavy metals (Cd, Cu, Fe, Ni, Pb and Zn) and 16 polycyclic aromatic hydrocarbons (PAHs). The ranges of the heavy metals in the plant (μg/g, dry weight) of this study for the respective metals are Cd: 0.01 – 5.11 μg/g, Cu: 4.05 – 139.03 μg/g, Fe: 18.10 – 2537.01 μg/g, Ni: 0.03-8.28 μg/g, Pb: 0.01 -31.59 μg/g, and Zn: 9.84 – 299.96 μg/g, while the ranges of PAHs concentrations (ng/g, wet weight) in the plant were 2 – 3 rings PAHs: 6.64 – 64.91 ng/g, 4 rings PAHs: 3.32 – 27.26 ng/g, and 5 – 6 rings PAHs: 1.42 – 226.37 ng/g. Topsoil from Sg. Kembung (S7), Juru (S18) and Kuala Terengganu (S21) have high concentrations of heavy metals and PAHs. Topsoil from these locations have high enrichment of heavy metals (EF > 20) and posed very strong ecological risk (ERI > 600). Furthermore, topsoil from these locations also can affected human health adversely. Present study determined highest toxicity equivalency factors (TEF) from S7 (34.28 ng/g), S18 (151.57 ng/g), and S21 (67.33 ng/g). The three sites also posed non-carcinogenic risk (HI > 1) and carcinogenic risk (Total Risk > 1 x 10-6) to adult and children in the area. Chemometric studies revealed that the three sites received significant input of mix sources of anthropogenic sources (heavy metals and PAHs). However, determination on the origin of anthropogenic sources was not possible due to lack of data. As for accumulation of contaminant in A. gangetica, plants sampled from Sg. Lembing (S13) and Juru (S18) generally accumulated higher heavy metals concentrations than other sites. Whereas, plant samples from Bidor (S4), Sepang (S6), Sg. Kembung (S7), and Kuala Krai (S11) generally contain higher PAHs than other sites. Accumulation behaviours of heavy metals in plants were generally consistent, however, increase of heavy metals in their habitat will induce changed in accumulations behaviours. Present study revealed that A. gangetica have higher uptake of Cu and Zn from topsoil to roots while having low translocations of Cu, Fe, and Zn. However, it was revealed that leaves and roots of the plant have similar accumulations behaviours of heavy metals. As for accumulations behaviours of PAHs, leaves usually accumulated more PAHs than other parts. Roots accumulated higher concentrations of 2-3 rings PAHs than 5-6 rings PAHs from topsoil. Translocations of PAHs in plants were low. Principal component analysis (PCA) and correlation suggested that there were no relationships of the pollutants between plants and topsoil. Present study suggested that A. gangetica can be a potential biomonitor, however, further studies are needed.